Green Initiative by Banking Sector In India - Krishnendu Ghosh (Eurasian Journal of Management & Social Sciences)
Go Green’ has become the new mantra across the globe. To implement the mantra successfully a huge amount of funding as well as awareness is very important. The financial industry can play a pivotal role. Green Finance has evolved as an emerging field of study in the 21st century. Green Banking has become one of the main elements of Green Finance. Green initiatives by the banking sector have emerged as a paradigm shift in traditional banking worldwide towards sustainable development. The purpose of this paper is to highlight the Green Banking practices adopted in India and their significance towards environmental protection and sustainable ecological balance. The methodology used for the article is mainly the theoretical framework build based on the various secondary sources like published articles, websites, government reports, etc. This study could benefit policymakers and researchers in understanding the various green initiatives taken by the banking sector in India as well as the challenges and way forward.